2017
DOI: 10.1161/jaha.117.007507
|View full text |Cite
|
Sign up to set email alerts
|

Total Bilirubin in Prognosis for Mortality in End‐Stage Renal Disease Patients on Peritoneal Dialysis Therapy

Abstract: BackgroundEvidence regarding bilirubin's antioxidant properties and predictive roles is growing. However, it is unclear whether serum bilirubin would have a prognostic impact on survival of patients with regular peritoneal dialysis.Methods and ResultsWe used the Taiwan Renal Registry Data System utilizing its 2005‐2012 data set. Data from patients on regular peritoneal dialysis were retrieved. The primary end point of observation was 3‐year mortality. A total of 3704 patients (mean age 53.5 years, 44% male) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
5
11
0
Order By: Relevance
“…In contrast, our study showed that among PD patients, the higher TBil group had a higher mortality risk than that of the lower TBil group, which is consistent with a study by Yang et al. [16], which indicated that PD patients with a high TBil ( > 0.6 mg/dl) had higher all-cause mortality. However, this study did not focus on the associations between the DBil or IBil and the mortality risk of PD patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, our study showed that among PD patients, the higher TBil group had a higher mortality risk than that of the lower TBil group, which is consistent with a study by Yang et al. [16], which indicated that PD patients with a high TBil ( > 0.6 mg/dl) had higher all-cause mortality. However, this study did not focus on the associations between the DBil or IBil and the mortality risk of PD patients.…”
Section: Discussionsupporting
confidence: 92%
“…[28] was Belgian, who cannot represent Asians well. We showed above that the findings of other studies of Asian populations are consistent with ours [14,16]. These factors may have caused the variations between our results and those of others and there are other possible explanations for these different results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the second outcome, de ned as the incidence of a combined renal end point, which was the rst of the following: a 30% decline in eGFR with a follow-up eGFR <60 mL/min/1.73 m 2 , death from renal causes, or initiation of renal replacement therapy, we report an inverse association with concentrations of serum albumin, serum bilirubin and haemoglobin and a positive association with concentrations of GGT and ALP Our study supports the emerging evidence that high bilirubin concentrations may be protective against decline in kidney function and poor renal outcomes. We have previously reported from the eGFR study the inverse association of log-bilirubin with UACR [9].Several other studies suggest a protective role of high serum bilirubin against progression of chronic kidney disease and poor renal outcomes and this may be related to delaying progression of brosis-related kidney disease [18][19][20][21][22][23] In our study of participants with high risk of CKD, there was a statistically signi cant decrease in the baseline concentrations of serum ALT across categories of decreasing eGFR. However, there was no signi cant relationship between baseline concentration of serum ALT and the annual decline in eGFR.…”
Section: Discussionsupporting
confidence: 54%
“…against progression of chronic kidney and poor renal outcomes and this may be related to delaying progression of brosis-related kidney disease [18][19][20][21][22][23] In our study of participants with high risk of CKD, there was a statistically signi cant decrease in the baseline concentrations of serum ALT across categories of decreasing eGFR. However, there was no signi cant relationship between baseline concentration of serum ALT and the annual decline in eGFR.…”
Section: Discussionmentioning
confidence: 67%